Status Penyakit Layu pada Tanaman Cabai Rawit (Capsicum Frutescens L.) di Banjarangkan, Klungkung - SUDARMA, I MADE; PUSPAWATI, NI MADE; SUNITI, NI WAYAN; BAGUS, I GUSTI NGURAH (Agrotrop : Journal on Agriculture Science; Vol 4 No 2 (2014), 2015)
Status of wilt disease in pepper (Capsicum frutescens L.) at Banjarangkan, Klungkung. Wilt disease in pepper , has led to a total yield loss in Banjarangkan, Klungkung regency. Until now the disease was still a threat to farmers in the area pepper. The purpose of research to study the disease includes symptoms, causes disease, the percentage of the disease and the rate of infection (r). Research using existing observations of the disease in three plots of local farmers. Each plot the observed number of diseased plants and entire plants. Samples of diseased plants put in a plastic bag, then placed in an ice box , to be observed macroscopically in the laboratory. The study was conducted in two places, namely surveys Banjarangkan disease in Klungkung , and isolation of the pathogen as well as pathogenicity test carried out in the Laboratory of Plant Pathology, Faculty of Agriculture, Udayana University, Jl. PB Sudirman Denpasar-Bali. The research was conducted from June to November 2013. The results showed that the pathogen that causes wilt disease in pepper at Banjarangkan, Klungkung regency was the fungus Fusarium oxysporum f.sp. capsici, with the disease incidence was 76.67%. Fusarium wilt disease epidemic in pepper indicated by the rate of infection, first gained 0.44 per unit per day, then decreases with time, 0.23, 0.12 and 0.11 per unit per day respectively. The rate of infection ranged from 0.11 to 0.44 per unit per day, this means that the moderate criteria.
Keywords: Wilt disease; Fusarium oxysporum F.Sp. Capsici; Disease incidence; Infection rate